Development of performance and safety monitoring system for low cost ultrasound medical device for prenatal diagnosis - Supriyanto, Eko; Ramli, Norhafizah (Faculty of Electrical Engineering, 2008)
Ultrasound is widely used in prenatal diagnosis. This is due to the easier, safer and lower cost compared to other medical imaging modalities such us CT â€“ scan, MRI and gamma ray. The advancement of microelectronic technology according to Moore law has enabled the production of low cost ultrasound machines. In 2007, there were about 200.000 low cost ultrasound machines worldwide. It is predicted that the number of these machines will increase and achieve 500.000 machines in year 2011. Survey result shows the most low cost ultrasound machines have lacking in performance and safety. This may cause an undesired diagnostic result that may be danger for patients. In order to reduce the undesired effect of ultrasound for patient diagnostic, a performance and safety monitoring system has been developed. The system is focused to improve the quality of service in prenatal diagnosis using ultrasound B scanning mode. According to the clinical survey and the draft of code of ultrasound in medical diagnostic there are two safety parameters to be monitored or tested before using ultrasound for medical diagnostic, they are the electrical leakage current and ultrasound intensity. Beside safety parameters, it is also required to monitor or test the performance of ultrasound. The performance parameters include dead zone, uniformity, depth of penetration, axial and local resolution, high scatter object diameter, vertical and horizontal distance. This project developed hardware and software to monitor the electrical leakage current called â€œleakage current meterâ€? and a device to test ultrasound power and intensity called â€œultrasound power meterâ€?. Improvement and measurement of ultrasound performance has Development of performance and safety monitoring system for low cost ultrasound medical devices for prenatal diagnosis iv been done by development of additional hardware and software device called â€œsonoimprometerâ€?. The leakage current meter has been developed according to IEC 60601-1. The meter can measure the patient, enclosure and earth leakage current with resolution of 1 ÂµA with range of 0 to 500 ÂµA. The meter consists of current electrode, amplifier, ADC, microcontroller and computer with monitor. The measurement result can be seen in computer display. The ultrasound power mater has been developed by using double polymer sensor called polyvinylidene fluoride (PVDF). The meter has been designed according to IEC 60601-2- 37 and IEC 60601 of the safety requirement for ultrasound in medical diagnostic and therapeutic. The meter is able to measure the ultrasound power from therapeutic and diagnostic machine with frequency range of 20 kHz to 10 MHz and power range of 0 to 30 W with resolution of 30 mW. The output is displayed on LCD and transferred to PC through USB for further analysis. The sonoimprometer has been created to measure and improve the ultrasound image quality. The meter is connected to ultrasound machine through USB and BNC connector. This system can capture the ultrasound image from low cost ultrasound machine. The captured image is stored in sonoimprometer and processed in order to have the value of some image quality parameter according to American Association of Physicist in Medicine. The meter is able to improve the resolution, contrast and geometry accuracy of measured images. All of developed device has been tested in laboratory and clinic to characterize the functionality, safety, stability and reliability. The test result shows that the sonoimprometer can be used by most low cost ultrasound machines to test their safety and performance. This sonoimprometer has been also presented in two competitions; they were NRIC and INATEX 2008, and won gold medal and special award. The products have been also registered to patent agent approval as novel products. The developed product is low cost, small in size, user friendly and has big market potential. The system Development of performance and safety monitoring system for low cost ultrasound medical devices for prenatal diagnosis v not only can monitor the performance, it is also capable to measure the safety of ultrasound machine. This machine can be used in private clinics, healthcare centres, home, research centres and ultrasound machine manufacturer, distributor and maintenance companies. It is estimated that about 400 products required yearly in Malaysia only. In order to penetrate Malaysia and international market, certifications of the product are required such as SIRIM, MOH and TUV. A business plan proposal for pre commercialization is recommended to be created and applied to MOSTI, such as TECHNOFUND or INNOFUND. Cooperation with companies is required for development, product commercialization and marketing.